Effect of fiber misalignment on mechanical and failure response of kenaf composite under compressive loading / M. F. Razali, S.A.H.A. Seman and T. W. Theng - Razali, M. F.; Seman, S.A.H.A.; Theng, T. W. (Universiti Teknologi MARA, 2021)
The use of kenaf fibres has grown unexpectedly in the world as they help to establish green materials in automobile, sports and food packaging industries. Over the past few decades, unidirectional fiber-reinforced composites have been extensively used in industry due to their high specific strength characteristics. During manufacturing process, several defects especially fiber misalignment might exist in the unidirectional composite structure. This kind of deviation from its optimal parallel packing in a unidirectional fibre reinforced composite would influence its overall load-bearing efficiency. Performance data of kenaf composite due to this imperfection, however, is very limited in the literature. In this regard, the effects of fibre misalignments on the unidirectional kenaf composite compressive reaction have been studied. For this reason, pultruded kenaf composite specimens with different fibre alignment from 00 to 20 at 2.1 and 8.4 mm/s strain rates were subjected to a range of compression measures. The findings revealed that, the failure strain seems to be almost constant at value of 0.05 and 0.063 while the failure stress decreases from 140Mpa until 120MP when the fibre alignment increases when loaded within a range of 2.1~8.4s-1 . Additionally, under increased fiber misalignment and strain rate, fibre plastic microbuckling, fibre breakage, fibre splitting and fibre matrix debonding was progressively formed on the specimen.